2008
DOI: 10.1128/mcb.00157-08
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proteins Associating with Glycosylphosphatidylinositol- Anchored T-Cadherin on the Surface of Vascular Endothelial Cells: Role for Grp78/BiP in T-Cadherin-Dependent Cell Survival

Abstract: There is scant knowledge regarding how cell surface lipid-anchored T-cadherin (T-cad) transmits signals through the plasma membrane to its intracellular targets. This study aimed to identify membrane proteins colocalizing with atypical glycosylphosphatidylinositol (GPI)-anchored T-cad on the surface of endothelial cells and to evaluate their role as signaling adaptors for T-cad. Application of coimmunoprecipitation from endothelial cells expressing c-myc-tagged T-cad and high-performance liquid chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 60 publications
6
104
0
Order By: Relevance
“…In line with that, it was shown that T-cadherin mediated activation of PI3K/Akt/GSK3β signaling which protects endothelial cells from oxidative stressinduced apoptosis (Joshi et al, 2005). The effects of T-cadherin on Akt activation and survival require T-cadherin interacting partner Grp78, which is also known to be upregulated in cancers Philippova et al, 2008). High molecular weight adiponectin activates NF-kB and inhibits endothelial cell apoptosis suggesting that T-cadherin binding to adiponectin could prevent apoptosis of endothelial cells in tumor vessels (Adachi et al, 2006).…”
Section: T-cadherin Structure and Intracellular Signalingmentioning
confidence: 67%
“…In line with that, it was shown that T-cadherin mediated activation of PI3K/Akt/GSK3β signaling which protects endothelial cells from oxidative stressinduced apoptosis (Joshi et al, 2005). The effects of T-cadherin on Akt activation and survival require T-cadherin interacting partner Grp78, which is also known to be upregulated in cancers Philippova et al, 2008). High molecular weight adiponectin activates NF-kB and inhibits endothelial cell apoptosis suggesting that T-cadherin binding to adiponectin could prevent apoptosis of endothelial cells in tumor vessels (Adachi et al, 2006).…”
Section: T-cadherin Structure and Intracellular Signalingmentioning
confidence: 67%
“…For example, binding of activated 2-macroglobulin to GRP78 induces the UPR and cancer cell proliferation (Misra et al, 2006). Interaction of GRP78 with cell surface T-cadherin promotes endothelial cell survival (Philippova et al, 2008). In a recent study, surface-expressed citrullinated GRP78 on monocytes/macrophages was found to bind anti-CCP antibodies and stimulate TNF production (Lu et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…This result might be explained by the possible positive feedback mechanism in which the over-expressed C-ERC could enhance the endogenous gene expression, and could be another aspect for biological malignancy of mesothelin. GPI-anchored proteins such as T-cadherin can transduce molecular signals that modulate cell migration and invasion with integrin-linked kinase [34] and integrin β3 [35]; in addition, an association between the expression of integrin and mesothelin in malignant pleural mesothelioma was reported using gene array [21].…”
Section: Discussionmentioning
confidence: 99%